The prevalence of sexual dysfunction, anxiety and depression in pre-dialysis chronic kidney disease patients in Uyo, Nigeria - Akpan EE; Udo AIA; Umoh AV (Ibom Medical Journal)
Background: Chronic kidney disease (CKD) is a progressive condition that spans years or even decades. It is therefore associated with comorbidities as well as other complications among which include erectile dysfunction (ED), anxiety, and depression.